2005
DOI: 10.1002/qua.20557
|View full text |Cite
|
Sign up to set email alerts
|

Large first hyperpolarizabilities of substituted aniline oligomers

Abstract: Substituted and nonsubstituted aniline oligomers were theoretically investigated. Aniline oligomers with a dicyanoethenyl acceptor group attached at a terminal site of each known structure (emeraldine, pernigraniline, and leucoemeraldine forms), contributing to obtain large first hyperpolarizabilities. The effect of oligomer size on the nonlinear responses was also investigated by considering oligomers with different chain length (tetramers and octamers). The magnitudes of ␤ calculated for the functionalized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 35 publications
(65 reference statements)
1
22
0
Order By: Relevance
“…Several systems characterized in the literature having the strong acceptor dicyanovinyl display very low energy transitions for the charge transfer processes, which contribute to the increase in the nonlinear coefficients 94, 95. In addition, theoretical studies revealed large nonlinear responses for various polyenic and aniline derivatives with the acceptor dicyanovinyl group 2, 25, 87, 88, 96, 97. Several experimental and theoretical studies have shown that the magnitude of the first hyperpolarizability of organic molecules is associated with lower values of the HOMO–LUMO gap 2, 3, 24, 56, 57, 96–99.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several systems characterized in the literature having the strong acceptor dicyanovinyl display very low energy transitions for the charge transfer processes, which contribute to the increase in the nonlinear coefficients 94, 95. In addition, theoretical studies revealed large nonlinear responses for various polyenic and aniline derivatives with the acceptor dicyanovinyl group 2, 25, 87, 88, 96, 97. Several experimental and theoretical studies have shown that the magnitude of the first hyperpolarizability of organic molecules is associated with lower values of the HOMO–LUMO gap 2, 3, 24, 56, 57, 96–99.…”
Section: Resultsmentioning
confidence: 99%
“…Oligomers have been studied because of their solubility in common solvents and their ability to be crystallized. These properties are different from the polymers themselves, and therefore, allow for their chemical processing 22–25. These features are essential for the construction of devices from mono‐ and multilayer films, single crystals, and other forms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations